Modern Psychoactive Substances and Their Detection in Biomedical Samples - A. M. Grigoryev; V. N. Fateenkov (Вестник войск РХБ защиты)
Scientific and technological advancement of the mid- and late twentieth century led to the creation of a large number of new psychoactive substances (NPS), diverse in composition and spectrum of action. The primary stages of fight the spread of NPS are awareness of their characteristics, as well as the possibility of detecting both the substances themselves and biomarkers of their use (metabolites) in human biological objects. The purpose of the work is to review psychoactive compounds and methods of their detection performed for diagnostic purposes. The paper presents brief characteristics of the most common NPS, as well as features of their metabolism in the human. It is shown that the analysis of biological specimens collected from susceptive drug users is difficult due to the low content of analytes, the matrix influences, metabolism and the formation of various artifacts. The general scheme of screening of biological objects assumes the presence of two stages – a preliminary express analysis performed using immunochemical test systems, and a confirmatory analysis performed by gas and liquid chromatography-mass spectrometry. The article discusses the possibilities and limitations of targeted and non-targeted screening. The subject of special consideration was the problems of using chromatography-mass spectrometry methods of NPS analysis in Russian – issues of accessibility of standard substances, search libraries, etc. The article also presents brief characteristics of individual families of NPS, such as stimulants, synthetic cannabinoids, synthetic opioids and hallucinogens. In addition, the article shows that in a number of foreign armies, in particular, in the Armed forces of Ukraine (AFU), drugs and psychostimulants are used to create «fearless soldiers». Thus, methadone, amphetamine and other psychoactive substances, as well as a psychotomimetic – a structural and pharmacological similarity of the prohibited BZ – were found in objects delivered from the positions of the AFU for analysis.